Myocardial tissue and metabolism characterization in men with alcohol consumption by cardiovascular magnetic resonance and 11C-acetate PET/CT - Shuai Liu; Xue Lin; Ximin Shi; Ligang Fang; Li Huo; Fei Shang; Juhani Knuuti; Chunlei Han; Xiaomeng Wu; Rui Guo; Haiyan Ding; Runhua Zhang; et al. (BMC, 2022)
Background: Chronic alcohol consumption initially leads to asymptomatic left ventricular dysfunction, but can result in myocardial impairment and heart failure if ongoing. This study sought to characterize myocardial tissues and oxidative metabolism in asymptomatic subjects with chronic alcohol consumption by quantitative cardiovascular magnetic resonance (CMR) and 11C-acetate positron emission tomography (PET)/computed tomography (CT).
Methods: Thirty-four male subjects (48.8 +/- 9.1 years) with alcohol consumption > 28 g/day for > 10 years and 35 age-matched healthy male subjects (49.5 +/- 9.7 years) underwent CMR and 11C-acetate PET/CT. Native and post T1 values and extracellular volume (ECV) from CMR and Kmono and K1 from PET imaging were measured. Quantitative measurements by CMR and PET imaging were compared between subjects with moderate to heavy alcohol consumption and healthy controls, and their correlations were also analyzed.
Results: Compared to healthy controls, subjects with alcohol consumption showed significantly shorter native T1 (1133 +/- 65 ms vs. 1186 +/- 31 ms, p < 0.001) and post T1 (477 +/- 42 ms vs. 501 +/- 38 ms, p = 0.008) values, greater ECV (28.2 +/- 2.2% vs. 26.9 +/- 1.3%, p = 0.003), marginally lower Kmono (57.6 +/- 12.1 min(- 1) x 10(- 3) vs. 63.0 +/- 11.7 min(- 1) x 10(- 3), p = 0.055), and similar K1 (0.82 +/- 0.13 min(- 1) vs. 0.83 +/- 0.15 min(- 1), p = 0.548) after adjusting for confounding factors. There were no significant differences in CMR measurements and K1 between subjects with heavy and moderate alcohol consumption (all p > 0.05). In contrast, subjects with heavy alcohol consumption showed significantly lower Kmono values compared to those with moderate alcohol consumption (52.9 +/- 12.1 min(- 1) x 10(- 3) vs. 63.7 +/- 9.2 min(- 1) x 10(- 3), p = 0.012). Strong and moderate correlations were found between K1 and ECV in healthy controls (r = 0.689, p = 0.013) and subjects with moderate alcohol consumption (r = 0.518, p = 0.048), respectively.
Conclusion: Asymptomatic men with heavy alcohol consumption have detectable structural and metabolic changes in myocardium on CMR and 11C-acetate PET/CT. Compared with quantitative CMR, 11C-acetate PET/CT imaging may be more sensitive for detecting differences in myocardial damage among subjects with moderate to heavy alcohol consumption.